Characteristics of cerebral ischemia in major rat stroke models of middle cerebral artery ligation through craniectomy. Issue 6 (4th December 2012) - Shmonin, Alexey; Melnikova, Elena; Galagudza, Michael; Vlasov, Timur
<x xml:space="preserve">Abstract</x> Background The refinement of experimental stroke models is important for further development of neuroprotective interventions. Aims and/or hypothesis Our goal was to study the reproducibility of outcomes obtained in five rat models of middle cerebral artery (MCA) ligation in order to identify the optimal model for the preclinical studies. Methods In Part 1 of the experiments, systolic blood flow velocity (sBFV) and cerebral area at risk (AR) were determined immediately after the onset of brain ischemia induced in different ways in Wistar rats. After that, another set of experiments was performed (Part 2 of the experiments), now aimed at the assessment of the delayed outcome of five different models of cerebral ischemia designated as Versions 1–5. The versions were: Version 1 – 40‐minute left MCA (LMCA) occlusion with reperfusion; Version 2 – permanent LMCA ligation; Version 3 – permanent ligation of both LMCA and left common carotid artery (CCA); Version 4 – permanent LMCA and bilateral CCA (bCCA) ligation; Version 5 – permanent LMCA ligation and 40‐minute bCCA occlusion. The infarct size (IS) was quantified using triphenyltetrazolium chloride staining. The severity of neurological deficit was assessed by the Garcia score. The extent of brain edema was determined by calculating the difference in volumes of affected and contralateral hemispheres. Results Within a relatively big AR, Versions 1 and 2 resulted in a small IS [0·2 (0·0; 0·4)% and 0·3 (0·0; 0·7)%, respectively, P > 0·05]. Unlike that and comparable with AR, Version 3 resulted in a greater, albeit more variable IS [5·9 (2·1; 8·3)%, P < 0·0001 vs. Version 2]. Also comparable with AR, Versions 4 and 5 produced greatest values of IS [14·5 (11·4; 17·9)% and 11·3 (10·1; 14·2)%, respectively]; this parameter was most reproducible in Version 5. A significant decrease in neurological deficit score was found in Versions 4 and 5. Again, the reproducibility of the data on neurological outcome was higher in Version 5 versus Version 4. Conclusions Comparative analysis of several Versions of focal cerebral ischemia within a single study might be helpful in better understanding of the mechanisms underlying the development and aftermath of stroke. Permanent LMCA ligation plus transient bilateral CCA occlusion produced most consistent results and might be recommended for preclinical studies.